Perancangan Tempat Rekreasi Budidaya Ikan Di Cipondoh Tangerang - Romadhan, Muhammad Ilham; Kurniasih, Sri; Kurniawan, Dody (MAESTRO, 2021)
ABSTRACT The development of advances in cultivation technology and supported by increasingly modern means of transportation, fish farming is now increasingly being carried out by the community. Among other things, this is also driven by a fairly good market prospect with a wider reach. Tangerang City, precisely in the area of Cipondoh, Cipondoh District, has freshwater aquaculture activities, due to the direction of the Tangerang city government which directs fisheries activities in the reservoir/Situ area. Also, the Cipondoh situ area according to the Tangerang City RTRW 2012-2032 is planned as a tourism activity. Based on the description that has been explained, the author has an idea to design a recreation area that involves fish cultivation activities and is located in Cipondoh District, Tangerang City.